2016
DOI: 10.1097/aln.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Care Transitions Are Not Associated with Postoperative Adverse Outcomes

Abstract: Background Whether anesthesia care transitions and provision of short breaks affect patient outcomes remains unclear. Methods The authors determined the number of anesthesia handovers and breaks during each case for adults admitted between 2005 and 2014, along with age, sex, race, American Society of Anesthesiologists physical status, start time and duration of surgery, and diagnosis and procedure codes. The authors defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 11 publications
1
52
0
1
Order By: Relevance
“…Hudson et al found an important link between intraoperative handovers during cardiac surgery and in-hospital mortality, and a similar association was found among patients undergoing other forms of surgery. 13 However, a recent study by Terekhov et al 18 did not find that the number of anaesthesia handovers was associated with increased odds of postoperative mortality and serious complications. To date, all studies on intraoperative anaesthesia handovers and morbidity/mortality have analysed only retrospective data and are thus subject to significant methodological limitations, such as bias resulting from confounding factors (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hudson et al found an important link between intraoperative handovers during cardiac surgery and in-hospital mortality, and a similar association was found among patients undergoing other forms of surgery. 13 However, a recent study by Terekhov et al 18 did not find that the number of anaesthesia handovers was associated with increased odds of postoperative mortality and serious complications. To date, all studies on intraoperative anaesthesia handovers and morbidity/mortality have analysed only retrospective data and are thus subject to significant methodological limitations, such as bias resulting from confounding factors (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…To date, all studies on intraoperative anaesthesia handovers and morbidity/mortality have analysed only retrospective data and are thus subject to significant methodological limitations, such as bias resulting from confounding factors (e.g. the study by Terekhov et al 18 was performed at an institution where a detailed PACU handover protocol with teaching sessions had just been implemented).…”
Section: Discussionmentioning
confidence: 99%
“…(1) In contrast, a prior examination of over 140,000 anesthetics within a large American university hospital, adjusted for case severity, duration, surgical complexity, and patient comorbidities, found no association between handoffs and adverse outcomes. (7) Effect estimates vary widely within other similar investigations. (2,8,9) We sought to further examine the association between handoffs of anesthetic care in our care team…”
Section: Introductionmentioning
confidence: 87%
“…[6] In contrast, a prior examination of over 140,000 anesthetics within a large American university hospital, adjusted for case severity, duration, surgical complexity, and patient comorbidities, found no association between handoffs and adverse outcomes. [7] Effect estimates vary widely within other similar investigations. [1,8,9] We sought to further examine the association between handoffs of anesthetic care in our care team model and a composite measure of adverse postoperative outcomes using The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP), as its definitions have been validated.…”
Section: Introductionmentioning
confidence: 87%
“…Conversely, handoffs allow for rested personnel to assume care, heighten vigilance and performance, and therefore possibly mitigate these risks. Estimates of handoff effects have varied widely in prior investigations; however, estimates of their effect in larger, more robust investigations have been modest [1,[6][7][8]. Effect estimates may therefore be influenced by sample size, case mix, and the relative balance of error introduction versus harm mitigation influenced by local practice.Another potential explanation for the incongruity of our results with prior investigations may be that local practice patterns or experience surrounding handoffs and postoperative care can mitigate their potential harm.…”
mentioning
confidence: 99%